Health care service in paediatric and adolescent gynaecology throughout Europe: A review of the literature. (April 2019) - Roos, Eveline J.; Vatopoulou, Anastasia; ,
Abstract: Background: Paediatric and adolescent gynaecology is a special field of interest within general gynaecology and obstetrics. The care for children and young people differs from adults. In gynaecology, children should not be treated like little adults. Within Europe, there is great variability in the provision of care, availability of clinical networks and lack of national standards within paediatric and adolescent gynaecology. Therefore, this review aims to summarize the current evidence regarding best clinical practice within Europe. Methods: A search was performed in Embase and Medline from 1974 onwards. Inclusion criteria were paediatric and adolescent population, gynaecology or reproductive health, care provision and evidence based clinical guidelines. In most papers recommendations were made, so no outcome measures could be used. It was, therefore, not possible to perform a meta-analysis. The risk of bias of the studies was assessed according to the GRADE and AGREE-2 guidelines. Results: 91 papers were identified and a total of 7 papers were included in the final analysis. The main recommendations are: - improvement for accessibility for healthcare facility, - training of healthcare staff in communication and examination according to developmental age, - develop evidence based clinical guidelines and standardize content of care delivered, - add training in general adolescent topics to training curriculum of paediatric and adolescent gynaecology. Conclusion and implications: There is limited information about best clinical practice and low quality of evidence of healthcare service available in the field of Paediatric and Adolescent Gynaecology. As a result there is a need to refine standards of training and care. EURAPAG should encourage adaptation of the unified standards of care in each European country. Furthermore, at this moment, there is insufficient inclusion of curriculum related to PAG in the undergraduate and post graduate training for recognition of patterns and symptoms in young women. EURAPAG should not only take a lead to develop common curriculum for undergraduate and post graduate education and training to address this unmet need but should also lead on their implementation within Europe.